Pengembangan Sistem Informasi Pengarsipan Surat untuk Meningkatkan Efisiensi Manajemen Dokumen - Anazariyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study aims to develop and implement a Letter Archiving Information System to enhance the efficiency of document management within organizations. The system is designed to automate the archiving process, ensuring accurate and organized storage of both incoming and outgoing correspondence. Key features include digital scanning of physical documents, metadata tagging, searchable database, automated categorization, and secure access controls. By utilizing advanced data management and optical character recognition (OCR) technologies, the system ensures that documents are easily retrievable and protected against loss or damage. The research discusses the design, development, and deployment phases of the system, including technology selection, system architecture, and user interface considerations. The system is evaluated based on its impact on operational efficiency, data accuracy, and user satisfaction. The results indicate that the implementation of the Letter Archiving Information System leads to significant improvements in document retrieval times, reduces physical storage requirements, and enhances overall document management practices. The paper also addresses the challenges encountered during the development and deployment of the system, along with the solutions implemented to ensure successful integration and user adoption.